Environmental Strategies in Hotel Industry: A Systematic Framework-Based Review and Future Research Directions (International Journal of Environmental Sciences, 2025)
Environmental strategies in the hotel industry (ESHI) have gained significant attention from practitioners, academicians, stakeholders, and policymakers. Implementing these strategies is vital to the environmental sustainability of the hotel industry. This review paper aims to synthesize the existing literature on environmental strategies and to provide a comprehensive understanding of the concept. For this purpose, a framework-based systematic review of 99 articles from the last twenty-four years was conducted. This review uses two organizing frameworks to provide comprehensive insights. The Antecedents, Decisions, and Outcomes (ADO) framework provides deep insight into the research domain. Additionally, the Theories, Contexts, and Methods (TCM) framework highlights theoretical foundations, contexts, and analysis methods used in the existing literature. Additionally, this review identifies research gaps in the current literature and provides future research directions using the two aforementioned frameworks. This study offers several important implications. It provides evidence-based guidance for practitioners on designing and implementing more effective and integrated environmental strategies. For policymakers, it underscores the need to create enabling regulatory and institutional environments that incentivize sustainable practices. The review maps future research directions for researchers by highlighting underexplored theoretical perspectives, methodological innovations, and emerging sustainability challenges, such as climate adaptation and circular economy practices in hospitality.